Relevansi Nilai-Nilai Pancasila dalam Era Digital: Studi Kasus Penggunaan Media Sosial - Rusda Karmila; Syamzaimar Syamzaimar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The digital era, with 78% internet penetration in Indonesia (2025), brings information advancement but also threats like cyberbullying, hoaxes, and SARA polarization through social media. This study aims to analyze the relevance of Pancasila values as an ethical filter in mitigating these negative digital impacts through social media usage case studies. Employing a qualitative approach based on library research, data was gathered from 18 Sinta-accredited journals (2021-2026), 2 Pancasila digital theory books, UU ITE regulations, and APJII reports. Content analysis with Miles & Huberman (2024) data reduction was applied to code the implementation of each Pancasila principle. Results show that the first principle combats religious intolerance, the second suppresses cyberbullying (25% reduction), the third reduces 2024 election polarization (40%), the fourth promotes digital deliberation, and the fifth closes rural literacy gaps through gotong royong crowdfunding (Rp1T collected). Viral disinformation and Lombok 2025 disaster cases prove Pancasila's effectiveness beyond formal regulations. It is concluded that Pancasila is adaptive as a moral algorithm in the digital era, transforming social media from conflict breeding grounds into national integration spaces. Recommendations include strengthening the